The war against America Saddam Hussein and the World Trade Center attacks : a study of revenge - Mylroie, Laurie (reganbooks, 2001)
The destruction of the twin towers of the World Trade Center and the attack on the Pentagon demonstrated America's vulnerability to terrorism. Yet terror had already emerged on America's shores eight years earlier, when the mysterious terrorist mastermind, Ramzi Yousef (arrested after a botched attempt to down a dozen U.S. airlines) bombed the World Trade Center in an attempt to fell the buildings. His attacks were viewed as the harbinger of a new terrorism, carried out by an enemy driven by religious fanaticism and hatred towards the United States. But is that perception accurate? This real-life detective story engages the reader in an examination of the evidence regarding Yousef and his terrorism. It reveals the split between New York and Washington that emerged during the investigation and tells of America left exposed and vulnerable following the mishandling of what was once the most ambitious terrorist attack attempted on U.S. soil.